MENINGKATKAN ETOS KERJA BERKUALITAS DAN KEPEDULIAN SOSIAL - ALMIZAN ALMIZAN (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2017)
The theme of research is business management based on Islamic principles. The purpose of this research is to look at work ethic and social concern. This study is a literature study. The Islamic work ethic is: a). Working to completion, b). Working with sincerity, c). Working honestly, d). Working with technology, e). Working with groups, f). Work hard, g). Working as a service.